Penilaian Kinerja Keuangan Ditinjau dari Rasio Likuiditas, Solvabilitas dan Profitabilitas (Studi Pada PT. Surya Bayu Sejahtera) - RAFLI ARDIANSYAH; Burhannudin Burhannudin (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2020)
Financial performance appraisal is intended to review and measure the achievement of the company against the initial planned objectives within a predetermined time frame. Financial ratio analysis can be used to assess the company's financial performance. This research was conducted with the aim to determine the financial performance of PT. Surya Bayu Sejahtera in 2014-2018 through the ratio of liquidity, solvency, and profitability. This research uses descriptive methods and uses secondary data. The results of this study showed that the liquidity ratio in 2014-2018 experienced fluctuations and the company was in less good condition. The solvency ratio in 2014-2018 is in good condition and continues to increase, even though in 2015 and 2016 the company has no debt. Profitability ratios during 2014-2018 tend to fluctuate and companies are in less good condition. Overall, the 2014-2018 ratio analysis tends to fluctuate and companies are in less good condition. This means that PT. Surya Bayu Sejahtera experiences ineffective problems in terms of the use of company funds, but this is not dangerous for the company because it will not cause bankruptcy for the company.